ANALYSIS OF ONLINE SPT POLICY IMPLEMENTATION AT KPP PRATAMA SUKABUMI - Rustiawan, Mulyana; Saleh, Munandi; Alamsyah, Sakti (Penerbit Lafadz Jaya, 2024)
Online Tax Return is a form of e-government as an effort to open public participation and improve the quality of public services. The latest online tax service is the electronic Tax Recipt Unification of Government Agencies which is relevant to the obligation for civil servants to use e-filing. This policy aims to improve public services. Government agencies are required to issue and report electronic proof of deduction, civil servants are required to report using e-filing as a form of compliance with regulations. The participation in the implementation of the Online Tax Return policy for Government Agencies and civil servants has not been achieved optimally. Researchers were interested in researching how these policies are implemented, what factors hinder and support them, and what innovations have been carried out. The object of research is the Implementation of Online Tax Returns with the locus of Sukabumi Primary Tax Office. The study uses qualitative methods, and model data analysis, with 6 (six) dimensions of Van Meter and Van Horn policy implementation theory variables. The results showed that the 6 research dimensions had been carried out effectively. However, the objectives and size of the policy have not been implemented optimally. There are government agencies and civil servants who have not reported tax returns due to obstacles. Some government agencies have not issued 1721-A2 proof of deduction using e-Bupot due to validation constraints NPWP and deposit. Several civil servants had not reported Online Tax Returns due to technical and non-technical constraints. Government agencies have made innovative efforts to overcome the obstacles encountered.